The Cost of Information: The Case of Constant Marginal Costs - Pomatto, Luciano; Strack, Philipp; Tamuz, Omer (American Economic Review, 2023)
We develop an axiomatic theory of information acquisition that captures the idea of constant marginal costs in information production: the cost of generating two independent signals is the sum of their costs, and generating a signal with probability half costs half its original cost. Together with Blackwell monotonicity and a continuity condition, these axioms determine the cost of a signal up to a vector of parameters. These parameters have a clear economic interpretation and determine the difficulty of distinguishing states. (JEL D82, D83)